Barriers to Effective Learning of High School Students in Turkey - Eda Gürlen; Tuğba Cihan (International Journal of Assessment Tools in Education)
This study aims to present the development and validation process of a scale to explore the learning barriers of high school students in Turkey. For this purpose, a scale was developed and administered to 316 high school students studying in the different counties of Ankara in the spring term of 2014-2015 academic year. Gathering the data, an exploratory factor analysis was run through SPSS Package program to see the structure of the interrelationships among the variables under six tests. Furthermore, a reliability analysis was conducted to the items under each test in the scale. As a result, one factor appeared under each test when the eigenvalues and variance percentages were examined, making six factors in total. The Cronbach’s Alpha Reliability Coefficient was calculated as to be significant for each test, which showed that the tests were reliable. Finally, some items were excluded from the scale.